Influence of Contextual Teaching and Learning (CTL) on Ability of Story and Concept of Numbers of Children Group A - Y. Setiyowati (Atthiflah: Journal of Early Childhood Islamic Education, 2020)
This study aims to determine the influence of Contextual Teaching and Learning (CTL) on ability of story and concept of numbers of children group A. Approach research in this study is quantitative research with experimental model design or quasi experimental design. Data collection techniques used are observation and documentation. Data analysis technique used is paired t-test. Based on the results of the analysis it can be concluded: (1) there is a difference in the ability to tell the story between before (pretest) and after (posttest) get CTL in the experimental group, so that there is a significant influence on the use of CTL on ability of story; (2) there are differences in the concept of numbers between before (pretest) and after (posttest) getting CTLs in the experimental group, so that there is a significant influence on the use of CTL on concept of numbers of children group A.